Communicating citizenship - social positioning in participatory decision making = Die Kommunikation von Staatsbürgerschaft - soziale Positionierung in partizipatorischen Entscheidungsprozessen - Bora, Alfons (2006)
"The proposed presentation has two aims: (a) It will outline a theoretical understanding of 'citizenship' that is rooted in sociological systems theory and in sociolinguistic approaches. With this approach it tries to develop a sociological supplement to the more normative notions of governance and citizenship in the legal and political sciences. (b) It will apply these theoretical considerations to a comparative view on forms of citizenship, which can be observed in participatory procedures in different European countries. The rationale of such a perspective is, at the end, to aim at a sociologically grounded evaluation of normative expectations about 'adequate' and 'legitimate' forms of participatory governance. The task or the problem that is being solved by the idea of citizenship has been remaining identical from the beginning of political reflection in the Greek polis to the modern concepts, such as Marshall's 'Citizenship and Social Class', Barber's notion of 'Strong Democra